Measuring experiences and concerns surrounding contraceptive induced side-effects in a nationally representative sample of contraceptive users: Evidence from PMA Ethiopia - Linnea A. Zimmerman; Dana O. Sarnak; Celia Karp; Shannon N. Wood; Mahari Yihdego; Solomon Shiferaw; Assefa Seme (Elsevier, 2022)
Objective: Our objectives were to assess the prevalence of specific side-effects experienced by current and recent contraceptive users, describe patterns of side-effects that users were concerned about, and share measurement lessons learned. Study design: Data come from the PMA Ethiopia 2019 nationally-representative, cross-sectional survey. Our analytic sample included women who were current (weighted n = 2190; unweighted n = 2020) or recent (past 24 months; weighted n = 627; unweighted n = 622) users of a hormonal method or IUD. We provide descriptive statistics of the percentage of current/recent users who report currently/ever experiencing specific side-effects, not experiencing but being concerned about experiencing specific side-effects, and both currently experiencing and being concerned about experiencing specific side-effects. All analyses are stratified by method type (implant, injectable, pill) to explore variation by method. Results: Among current users, 648/2190 women (30%) reported experiencing any side-effect, while 252/644 (40%) of recent users reported ever experiencing any side-effect. Bleeding changes were reported most frequently and were higher among implant and injectable users. More recent users reported side-effects that were associated with physical discomfort, such as headaches, than current users. About one-third of current and recent users reported being concerned about at least one side-effect that they had not experienced, with about 15% of current and recent users reporting concerns about bleeding changes (307/2190 and 112/627, respectively) and concerns about physical discomfort (334/2019 and 98/627, respectively). Conclusions: While bleeding changes are common, users report a range of side-effects related to physical discomfort underscoring the need for comprehensive counseling. We highlight challenges in measuring side-effects using quantitative tools and pose recommendations for future research and measurement efforts. Implications: : Experiencing and fearing contraceptive-induced menstrual bleeding changes and physical discomfort, particularly headaches, is high among hormonal contraceptive and IUD users in Ethiopia. counseling that addresses an array of side-effects is needed. Additional research is also needed to disentangle the effect of experiencing versus fearing side-effects on contraceptive use.